Phonon confinement effects in Raman spectra of porous silicon at non‐resonant excitation condition. (30th April 2014) - Kosović, Marin; Gamulin, Ozren; Balarin, Maja; Ivanda, Mile; Đerek, Vedran; Ristić, Davor; Marciuš, Marijan; Ristić, Mira
<x xml:space="preserve">Abstract</x> Light emitting porous silicon samples with different porosities, i.e. crystalline sizes, were produced from the low level doped p‐type silicon wafers by the anodization process. The effects of strong phonon confinement, redshift and broadening, were found on the O(Γ) phonon mode of the Raman spectra recorded at non‐resonant excitation condition using a near infrared 1064 nm laser excitation wavelength. Similarly, the blueshift of the photoluminescence peak was observed by reducing the crystalline sizes. Vibrational and optical findings were analysed within the existing models of confinement on the vibrational and electronic states of silicon nanocrystals. Since the energy of the photoluminescence peak of small nanocrystals also depends on the oxygen content on the surface of nanocrystals, the surface oxidation states were examined using infrared and energy dispersive spectroscopy. The partial coverage of the surface of nanocrystals was found due to the sample exposure to air. As a consequence, the photoluminescence energy did not increase as would be expected from the quantum confinement model. These results further indicate that the oxygen passivation along with the quantum confinement determines the electronic states of the silicon nanocrystals in porous silicon. Copyright © 2014 John Wiley & Sons, Ltd.